A Discussion on Postmodernism: György Ligeti’s Opera Le Grand Macabre - Duygu Küçük Özbek; Şebnem Ünal (Konservatoryum)
This research emerged from my Proficiency in Art thesis titled “Analysis of György Ligeti’s Opera Le Grand Macabre as an Example of Anti-Anti-Opera” and aims to analyze the musical structure and in particular the intellectual foundations of the opera Le Grand Macabre, composed by György Ligeti and an outstanding work in the 20th-century opera repertoire. This article analyzes the work to discuss its place in the modern and postmodern opera classification. Although György Ligeti had stated the work to classify not as postmodern but rather as anti-anti-opera in opposition to the anti-opera genre showing postmodern features, many experts have discussed the work since it appeared on stage in a way that was generally quite instructive in the qualitative analysis of modern and postmodern opera. The debates Le Grand Macabre created have had an important place in forming the intellectual and musical classifications in the history of 20th-century opera. This study firstly draws the conceptual, historical, and artistic framework of postmodernism, then provides basic information about the work, before finally arriving at the results in terms of the work’s modern and postmodern opera classifications. The study presents the example of where the opera Le Grand Macabre is placed by emphasizing it in the sense of how modern and postmodern opera emerged and developed over time, the philosophy on which it is based and the artistic phenomenon it has shaped. This study uses qualitative research with the aim of helping future research by making use of many sources that have not yet been translated into Turkish.